What is the Contribution of Intra-household Inequality to Overall Income Inequality? Evidence From Global Data, 1973-2013 - Deepak Malghan; Hema Swaminathan (Luxembourg Income Study (LIS), 2016)
Intra-household inequality continues to remain a neglected corner despite renewed focus on income and wealth inequality. Using the LIS micro data, we present evidence that this neglect is Equivalent to ignoring up to a third of total inequality. For a wide range of countries and over four decades, we show that at least 30 per cent of total inequality is attributable to inequality within the household. Using a simple normative measure of inequality, we comment on the welfare implications of these trends.
Keywords: 330; earnings; inequality; intra-household; Theil decomposition